Reconstruction of The Concept of Shirk in the Digital Era: A Thematic Analysis of the Qur’an on the Shift of Contemporary Aqidah - Firdaus Sinatra Firdaus Sinatra; Amrul Ahmad; Agung Pranoto Kadiatmaja (Universitas Samudra, 2026)
In the contemporary post-secular landscape, the manifestation of shirk (polytheism) has evolved from overt ritualistic idol-worship to subtle, functional equivalents within digital culture. This study aims to reconstruct the Qur’anic concept of shirk by examining its modern implications on the purity of aqidah (faith). Using a qualitative-descriptive approach grounded in library research, this study employs Tafsir Mawdu’i (thematic interpretation) to analyze relevant Qur'anic verses alongside modern sociological theories of digital alienation and self-apotheosis. The findings reveal that digital culture—characterized by algorithmic dependence, the sanctification of